ISGF3 with reduced phosphorylation is associated with constitutive expression of interferon-induced genes in aging cells - Yamagami, Mari (NPJ Aging Mech Dis, 2018)
During cellular aging, many changes in cellular functions occur. A hallmark of aged cells is secretion of inflammatory mediators, which collectively is referred to as the senescence-associated secretory phenotype (SASP). However, the mechanisms underlying such changes are unclear. Canonically, the expression of interferon (IFN)-stimulated genes (ISGs) is induced by IFNs through the formation of the tripartite transcriptional factor ISGF3, which is composed of IRF9 and the phosphorylated forms of STAT1 and STAT2. However, in this study, the constitutive expression of ISGs in human-derived senescent fibroblasts and in fibroblasts from a patient with Werner syndrome, which leads to premature aging, was mediated mainly by the unphosphorylated forms of STATs in the absence of INF production. Under homeostatic conditions, STAT1, STAT2, and IRF9 were localized to the nucleus of aged cells. Although knockdown of JAK1, a key kinase of STAT1 and STAT2, did not affect ISG expression or IFN-stimulated response element (ISRE)-mediated promoter activities in these senescent cells, knockdown of STAT1 or STAT2 decreased ISG expression and ISRE activities. These results suggest that the ISGF3 complex without clear phosphorylation is required for IFN-independent constitutive ISG transcription in senescent cells.